Keunggulan dan Strategi Model Bisnis Tape Singkong Kang Asep - Ria Anista; Ahmad Surya Pradana (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2023)
Cassava-based agroindustry plays an important role in supporting local economic development and strengthening micro, small, and medium enterprises (MSMEs) in Indonesia. One of the traditional products with high economic potential is cassava tape, which has long been developed using conventional business practices. However, increasing competition, changes in consumer behavior, and market dynamics require business actors to adopt effective and adaptive business models. This study aims to analyze the advantages and business model strategies implemented by the cassava tape enterprise “Kang Asep” as a form of value-added agroindustry development. This research employed a qualitative descriptive approach with a case study design. Data were collected through observations, in-depth interviews, and documentation, then analyzed using business model canvas and SWOT analysis. The results indicate that Kang Asep’s cassava tape business possesses competitive advantages in product quality consistency, traditional fermentation techniques, strong brand identity, and customer loyalty. Strategic implementation focuses on product differentiation, cost efficiency, utilization of local raw materials, and the integration of offline and online marketing channels. These strategies enable the business to enhance competitiveness and sustainability amid market challenges. The study concludes that an adaptive business model supported by local resource optimization is essential for strengthening cassava-based agroindustry performance. The findings are expected to contribute theoretically to MSME business model studies and practically to agroindustry development strategies.